2013
DOI: 10.4490/algae.2013.28.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation strategies of the temperate coralline alga Corallina officinalis: a perspective on photosynthesis, calcification, photosynthetic pigment contents and growth

Abstract: The coralline alga, Corallina officinalis, is a widely distributed intertidal species in temperate coastal regions. It is usually exposed to high fluctuations of light intensity, light quality, temperature, and desiccation, all of which affect the temporal and spatial distribution as well as the morphology and the metabolism of this alga. In laboratory experiments we examined the effects of different light intensities (50, 100, and 200 μmol photons m -2 s -1) on photosynthesis, calcification, photosynthetic pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(53 reference statements)
1
16
1
Order By: Relevance
“…However, alteration of pigment concentrations under different light environments has also been previously shown for Corallina species (e.g. Algarra et al, 1991;Häder et al, 1997;Kim et al, 2013). Thus, whilst it is not possible to differentiate the relative roles of high light-stress and changes in pigment concentrations on the seasonal patterns in photophysiology observed during the present study, it is likely that both components play a governing role.…”
Section: Seasonal Photoacclimation To Irradiancecontrasting
confidence: 39%
“…However, alteration of pigment concentrations under different light environments has also been previously shown for Corallina species (e.g. Algarra et al, 1991;Häder et al, 1997;Kim et al, 2013). Thus, whilst it is not possible to differentiate the relative roles of high light-stress and changes in pigment concentrations on the seasonal patterns in photophysiology observed during the present study, it is likely that both components play a governing role.…”
Section: Seasonal Photoacclimation To Irradiancecontrasting
confidence: 39%
“…Nighttime calcification rate ( G N ) was 4.1 times smaller than daytime calcification, a ratio close to 3.6 found in E. elongata at NW Mediterranean by El Haïkali et al (). In the absence of light, several coralline studies have found dissolution rather than calcification (Chisholm ; Kim et al ). In this study, however, net dissolution was found at 33°C and 35°C only, during both daytime and nighttime.…”
Section: Discussionmentioning
confidence: 99%
“…P Q peaked at 178C to a level of 1.25 and gradually decreased at higher temperatures. Other studies measured coralline P Q levels under variable irradiance (Kim et al 2013) and PCO 2 (Martin et al 2006) levels, and found no significant effects. The observed decline of P Q with temperature is possibly a result of photorespiration (Burris 1981).…”
Section: Photosynthesis Response To Warmingmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, large gradients of O 2 and CO 2 can exist within the rhodolith microhabitats, indicating photorespiration mechanisms could be very complicated along these chemical environments (Kim et al. 2013). These results indicate that larger rhodoliths exhibit lower mass‐specific rates of gross productivity but higher mass‐specific respiration than smaller rhodoliths, and thus lower mass‐specific rates of net productivity.…”
Section: Discussionmentioning
confidence: 99%